The potential of baru (Dipteryx alata Vog.) and its fractions for the alternative protein market - Egea, Mariana Buranelo; de Oliveira Filho, Josemar Gonçalves; Campos, Stephani Borges; Lemes, Ailton Cesar (Frontiers in Sustainable Food Systems, 2023)
The baru is a native fruit of the Brazilian Cerrado and its processing generates by-products that are normally undervalued and are not included in human food. Among the by-products of baru almond processing–the economically valued part for human consumption–are the broken almond, the partially defatted baru almond cake (DBC) and the pulp [composed of epicarp (peel) plus mesocarp]. Thus, this mini-review presents the potential use of baru (Dipteryx alata Vog.) and its fractions for the alternative protein market. Baru almond and its fractions (DBC and compounds obtained by different extraction methods) stand out for their high protein content (23–30 g/100 g) and, in particular, the by-products can be used as raw material for extraction, separation, hydrolysis, isolation, and concentration of the protein molecules to produce plant-based ingredients. Although it has great potential, including sensory, nutritional, and techno-functional properties, these by-products are still few studied for this purpose.